Oil Spill Cleanup by Hydrophobic Natural Fibers - Shengbin Cao; Ting Dong; Guangbiao Xu; Fu-mei Wang (Journal of Natural Fibers, 2017)
This article evaluates and compares on oil wetting and sorption performance of three natural fiber assemblies made by kapok, cattail and cotton fibers in application of absorbing vegetable oil. The three fibers were naturally hydrophobic and oleophilic. The water stood on the fibers’ surfaces with the contact angles between 120° and 145°, while oil droplet disappeared quickly from the fibers’ surfaces within several seconds. When applied as the oil sorbents, it was found that the three fiber assemblies showed quick oil uptake. Among them, kapok fiber assembly showed exceptionally high oil sorption and retention capacity. The presence of big hollow lumens which contributed to 77 % of the fiber’s volume was the important reason for this. Cattail fiber was bamboo-shaped. The fiber was short (3–11 mm). However, the formation of numerous of bamboo-liked lumens between neighboring fibers in cattail fiber assembly contributed to it quick oil sorption and excellent oil retention capacity, despite of relatively low oil absorbency. Although faster oil spreading comparing to kapok fibers, cotton fibers showed much lower oil absorbency and retention capacity, due to its collapsed lumens which considerably reduced its available pores for oil sorption.